Bioeconomy starts Local – a Case study on Multi-Level Participative Governance and Circular Bioeconomy Development in Romania - Sebestyén, Tihamér Tibor (Észak-magyarországi Stratégiai Füzetek, 2024)
This paper examines the implementation of a multi-level participative governance approach to address demographic change in rural areas, with a focus on the local rural municipality of Ghelinta. The paper will present through a case study approach, strategical responds on rural-urban challenges. The project responds to the rural exodus driven by better employment opportunities and prospects in urban areas were realized, resulting in depopulation and an aging, increasingly unskilled population in rural regions. Utilizing Circular-Bioeconomy as a tool for regional development, the Godanubio project fostered sustainable economic practices by transitioning from a fossil-resource-based economy to one that emphasizes biological resources and processes. This strategy aims to enhance value creation through new collaborations, business models, and value chains, thereby increasing the attractiveness of rural areas for young people. In Ghelinta, several working group meetings were conducted, involving young citizens in participatory governance and developing the 2021-2030 Local Bioeconomy Development Strategy. The key objectives of this strategy include fostering cooperation among local stakeholders, involving young people in the decision-making process within the local council, creating new business ideas in the bioeconomy sector, improving public services for young people, and providing training on bioeconomy topics. The overarching aims are to mitigate the gap between rural and urban areas, increase the visibility and attractiveness of rural areas through the development of the bioeconomy sector, and improve the overall well-being in rural regions. The long-term goal is to enhance the socio-economic status of these regions, contribute to environmental, climate, carbon sequestration and resource protection, and foster sustainable development (Sebestyen, 2024). This research highlights the importance of an ecosystem for systematic multi-level governance, engaging actors from the public, academia, industry, and political decision-making. By creating space for co-creation and integrated urban-rural cooperation, the project aims to increase institutional capacity to tackle demographic change and promote the active involvement of societal actors in the political system.